Efforts to Prevent Stunting by Conducting Socialization and Demonstration of Moringa Leaf Pudding Making in Glagahwero Village, Kalisat District, Jember Regency: Upaya Pencegahan Stunting dengan Melakukan Sosialisasi serta Demonstrasi Pembuatan Puding Daun Kelor di desa Glagahwero, kecamatan Kalisat, Kabupaten Jember - Fitriyatul Hanifiyah; Prima Cristi Crismono; Mely Agustin Reni Pitasari; Beby Dwi Febriyanti (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2024)
Stunting is a significant health issue in Indonesia today. For toddlers suffering from stunting, this can have long-term effects, such as disrupting their health education, and productivity in the future. The demonstration of moringa leaf pudding preparation was carried out to enhance knowledge and skills in the community so that they can understand and prevent stunting, as well as to showcase moringa leaf pudding as an alternative food or supplementary feeding to prevent stunting. The method used is an educational approach with the concept of lectures, along with information explanations and demonstrations on how to make moringa leaf pudding as a healthy food alternative to prevent stunting. The result of this activity is to provide an overview of the effectiveness of both activities in enhancing the knowledge and awareness of the community regarding the importance of moringa leaf pudding nutrition in preventing stunting. The output obtained is an increase in knowledge as well as an improvement in skills, along with publications in mass media and publications in scientific journals.